Ethics as a Primary Philosophy Introduction to the Philosophy of Emmanuel Levinas (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The philosophy of Emmanuel Levinas is considered as one of the most prominent contemporary philosophies. The renewing that presents this philosophy is related to the fact that it raises the ethics as a primary philosophy. Historically, it was the metaphysics - and later the ontology - that occupied this place, and this was because it ensured the discernment of the meaning of being. In order to accomplish this important shift, Levinas had to face the philosophy of Heidegger and his project of basic ontology. The bets that were caused by this move are very important, and they caused a major change in the treatment of the classic philosophical subjects. Levinas returns back to the commencement, to the commencement of the question, to the first astonishment of Greek philosophers, trying to give another meaning to this beginning. He also represents a complete reading of the philosophical history, based on this new perspective of the primary philosophy considered as ethics.